2016
DOI: 10.1002/cbin.10591
|View full text |Cite
|
Sign up to set email alerts
|

Sca‐1+mesenchymal stromal cells inhibit splenic marginal zone B lymphocytes commitment through Caspase‐3

Abstract: Mesenchymal stromal cells (MSCs) have been characterized as an important component of hematopoietic niche, which are capable of modulating the immune system through interaction with a wide range of immune cells. Marginal zone B cells, one main type of mature B lymphocytes, play a central role in eliciting antibody response against pathogens. However, how MSCs and its subpopulations regulate marginal zone B cells commitment is unknown yet. In this study, we assessed the contribution of Sca-1(+) MSCs on marginal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…MSCs were identified by PE anti-mouse CD44 (IM7, BD, U.S.A.), PE anti-mouse CD51 (RMV-7, eBioscience, San Diego, U.S.A.), APC anti-mouse CD90 (OX-7, BD, U.S.A.), APC anti-mouse CD105 (MJ7/18, BioLegend, California, U.S.A.), APC anti-mouse CD45 (30-F11, BioLegend, California, U.S.A.), and APC anti-mouse Ter119 (17-5921, eBioscience, San Diego, U.S.A.). The FACS plots showed that the surface markers of CD44, CD51, CD90, and CD105 were positive on MSCs, which was consistent with our previous reports [ 7 , 8 , 10 ]. MSCs were used for further experiments, when the CD45 negative Ter119 negative cells were up to 90%.…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…MSCs were identified by PE anti-mouse CD44 (IM7, BD, U.S.A.), PE anti-mouse CD51 (RMV-7, eBioscience, San Diego, U.S.A.), APC anti-mouse CD90 (OX-7, BD, U.S.A.), APC anti-mouse CD105 (MJ7/18, BioLegend, California, U.S.A.), APC anti-mouse CD45 (30-F11, BioLegend, California, U.S.A.), and APC anti-mouse Ter119 (17-5921, eBioscience, San Diego, U.S.A.). The FACS plots showed that the surface markers of CD44, CD51, CD90, and CD105 were positive on MSCs, which was consistent with our previous reports [ 7 , 8 , 10 ]. MSCs were used for further experiments, when the CD45 negative Ter119 negative cells were up to 90%.…”
Section: Methodssupporting
confidence: 92%
“…MSCs were obtained and characterized as our previous strategy [ 7 , 8 , 10 ]. In brief, tibias and femurs of C57BL/6 mice were obtained, and muscles and connective tissues were carefully removed from the bones with surgical scissors and razor blades.…”
Section: Methodsmentioning
confidence: 99%
“…+ MSCs A bone-related MSC mixture and Sca1 + MSCs were isolated using a previously described method (Wen et al, 2015;Chen et al, 2016aChen et al, , 2016b. Tibias and femurs were excised from mice of 8-12 weeks old.…”
Section: Preparation Of Mscs and Sca1mentioning
confidence: 99%
“…At P < 0.05, the difference was considered statistically significant. (Wen et al, 2015;Chen et al, 2016aChen et al, , 2016b + cells using the transwell system ( Figures 1D-1F). Taken together, these data suggest that Sca1 + MSCs promoted DC commitment and that cell-to-cell contact was needed for the promotion.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation